Management Of Funds And Economic Security In Universities In Cross River State - Francisca, Odigwe; Inyang, Okoi ikpi; Okpon, Ekaette samuel (Advances in Social Sciences Research Journal, 2015)
Recently, there have been reports on mismanagement and misappropriation of finances in universities. This study therefore, aimed at determining the relationship between management of funds and economic security in universities in Cross River State. The management of funds was examined in relation to internal audit system and budgetary control. Survey research design was adopted while the population of the study consisted of ninety (90) department heads from University of Calabar and Cross River State University of Technology (CRUTECH). Purposeful sampling technique was used and the sample size consisted of ninety departmental heads from the two universities. Questionnaire titled management of funds and economic security (MOFAESQ) was used. The reliability estimate was carried out using Cronbach reliability estimate (‘r’ -0.67 and ‘r’ – 0.74) Pearson Product moment correlation statistics was used for data analysis. The result of the findings revealed that there is a positive correlation between internal audit system, Budgeting control and economic security. It was therefore recommended that university management should ensure and establish an effective budgetary control system in order to control university expenditures. Moreso, university management should develop more strategies that will harness fully the various funds within the university. Key words: Management, Funds, Economic Security, Management of Funds, Management of Funds in Universities